B̄æp kānt̄æng kāp, kl̨ōn, khlōng, sōk, phayā, kl̨ōnlam, kl̨ōnʻān, kāp sārawilāsinī (K̨ōngthun Songs̄œm Ngān Watthanatham, Samnakngān Khana Kammakān Watthanatham h̄æng Chāt, 1996)
Construction of Thai prose.